Camila the stage star - Salazar, Alicia, 1973- (Salazar, Alicia, 1973- Camila the star., 2021)
"When Camila tries out for a play, she practices hard to get ready for auditions. So she's extra disappointed when she doesn't get the starring role. But as she learns her part and works with the rest of the cast, Camila discovers there is more than one way to be a star"--